Diabetic Complications and Insight into Antidiabetic Potentialities of Ethno-Medicinal Plants: A Review - Bilal, Muhammad; Iqbal, Muhammad S.; Shah, Syed B.; Rasheed, Tahir; Iqbal, Hafiz M.N. (Recent Patents on Inflammation & Allergy Drug Discovery, 2018)
Background: The naturally inspired treatment options for several disease conditions and human-health related disorders such as diabetes mellitus have gained considerable research interest. In this context, naturally occurring plants and herbs with medicinal functionalities have gained special place than ever before in the current medicinal world. Objective: The objective of this review is to extend the current knowledge in the clinical field related to the diabetic complications. A special focus has also been given to the anti-diabetic potentialities of ethnomedicinal plants. Method: Herein, we reviewed and compiled salient information from the authentic bibliographic databases including PubMed, Scopus, Elsevier, Springer, Bentham Science and other scientific databases. The patents were searched and reviewed from http://www.freepatentsonline.com. Results: Diabetes mellitus is a group of metabolic disorders associated with the endocrine system that resulted in hyperglycemic conditions. Metabolic disorders can cause many complications such as neuropathy, retinopathy, nephropathy, ischemic heart disease, stroke, and microangiopathy. Traditional botanical therapies have been used around the world to treat diabetes. Among several medications and different medicines, various herbs are known to cure and control diabetes; also have no side effects. History has shown that medicinal plants have long been used for traditional healing around the world to treat diabetes. More than 800 plants around the world are shown by ethnobotanical information as traditional remedies for the treatment of diabetes. Several parts of these plants have been evaluated and appreciated for hypoglycemic activity. Medicinal plants have been found to be more effective than conventional drug compounds with no/fewer side effects and relatively inexpensive. In this review paper, we have reviewed plants with anti-diabetic and related beneficial medicinal effects. Conclusion: This review may be helpful for researchers, diabetic patient and decision makers in the field of ethnobotanical sciences. These efforts may also provide treatment to everyone and focus on the role of traditional novel medicine plants that have anti-diabetic abilities.
Keywords: Antidiabetics